High-precision ice-flow velocities from ground observations on Dalk Glacier, Antarctica - Ai, Songtao; Wang, Shansi; Li, Yuansheng; Moholdt, Geir; Zhou, Chunxia; Liu, Leibao; Yang, Yuande (Polar Science, 2019)
Dalk Glacier, which has been monitored by CHINARE since 2007, is a calving outlet glacier near the Chinese Zhongshan Station in East Antarctica. Using in situ observational azimuthal data from 2007 to 2012, 67 high-precision spatial intersection points were calculated. Consequently, the ice-flow features of the tongue of Dalk Glacier were explored via ground measurements. The maximum observed ice-flow velocity (IV) was 192.72 m/a, at stake P9. The velocities then decreased with the distance from the central flow line on both sides of the glacier in a cross section. Further analysis showed the following: the velocities of each stake increased annually; the closer to the terminus, the faster the ice flowed; and the ascent ratio of the IVs was approximately 10.67 m/a2 in the main flow area. We also observed seasonal variations in the ice-flow velocities, including a speed-up in January 2009 preceding an ice-calving event. The elevation change measurements at the stakes showed fluctuations along the central flow line, which indicates ice-shelf grounding over a seamount that had not been previously identified.
Keywords: Antarktis; glasiologi

What and who is an Antarctic ambassador? - Alexander, Karen A.; Liggett, Daniela; Leane, Elizabeth; Nielsen, Hanne E. F.; Bailey, Jennifer L.; Brasier, Madeline J.; Haward, Marcus (Polar Record, 2019)
The term “Antarctic ambassadorship” is increasingly used to represent an individual’s connection to Antarctica and their subsequent advocacy. However, there is little clarity regarding the concept. To address this, we combined a literature review with an expert elicitation workshop. We argue that (i) the concept of Antarctic ambassador has been understood in myriad ways; (ii) Antarctic ambassadors have a connection to, knowledge of and passion for Antarctica; (iii) they also have a commitment to defending and advancing Antarctic values and (iv) Antarctic ambassadorship is about more than advocacy. We propose the first comprehensive definition of Antarctic ambassadorship. We hope this will provide a cornerstone upon which future research, and a more informed governance of Antarctic tourism, can be built.
Edition: 2020/05/20 Publisher: Cambridge University Press
Keywords: Antarktis; samfunnsfag

Warm Circumpolar Deep Water at the Western Getz Ice Shelf Front, Antarctica - Assmann, Karen; Darelius, Elin Maria K; Wåhlin, Anna K; Kim, Tae Wan; Lee, Sang Hoon (Geophysical Research Letters, 2019)
The Getz Ice Shelf is one of the largest sources of fresh water from ice shelf basal melt in Antarctica. We present new observations from three moorings west of Siple Island 2016–2018. All moorings show a persistent flow of modified Circumpolar Deep Water toward the western Getz Ice Shelf. Unmodified Circumpolar Deep Water with temperatures up to 1.5 °C reaches the ice shelf front in frequent episodes. These represent the warmest water observed at any ice shelf front in the Amundsen Sea. Mean currents within the warm bottom layer of 18–20 cm/s imply an advection time scale of 7 days from shelf break to ice shelf front. Zonal wind stress at the shelf break affects heat content at the ice shelf front on weekly to monthly time scales. Our 2-year mooring records also evince that upwelling over the shelf break controls thermocline depth on subannual to annual time scales.
Keywords: Antarktis; geofysikk; glasiologi; isbrem; isshelf; observasjoner

Chr. Christensen and C. A. Larsen: A comparative analysis of two whaling entrepreneurs - Basberg, Bjørn L (International Journal of Maritime History, 2019)
Keywords: Antarktis; historie; hvalfangere; hvalfangst

The Four Ladies of Prydz Bay: notes on the naming of a submarine formation in Australian Antarctic Territory - Bathie, Carol; Pett, Janet (The Victorian Naturalist, 2019)
Publisher: Field Naturalists Club of Victoria
Keywords: Antarktis; Nordmenn; ekspedisjoner; oppdagelsesreiser

Nitrogen isotope fractionation explains the 15N enrichment of Antarctic cryptogams by volatilized ammonia from penguin and seal colonies - Bokhorst, Stef; van Logtestijn, Richard; Convey, Peter; Aerts, Rien (Polar Research, 2019)
Vegetation near bird and seal rookeries typically has high δ15N signatures and these high values are linked to the enriched δ15N values of rookery soils. However, Antarctic cryptogams are mostly dependent on atmospheric ammonia (NH3) and volatized NH3 from rookeries is severely depleted in δ15N-NH3. So there is an apparent discrepancy between the isotopically depleted source (NH3) and δ15N-enriched vegetation. In this article, we aim to resolve this discrepancy to better understand the mechanisms and processes involved in isotopic changes during nitrogen transfer between Antarctic marine and terrestrial ecosystems. Under laboratory conditions, we quantified whether volatized NH3 affects the isotopic signature of cryptogams. NH3 volatilizing from penguin guano and elephant seal dung was depleted (44–49‰) in δ15N when captured on acidified filters, compared to the source itself. Cryptogams exposed to the volatized NH3 were enriched (18.8–23.9‰) in δ15N. The moss Andreaea regularis gained more nitrogen (0.9%) than the lichen Usnea antarctica (0.4%) from volatilized NH3, indicating a potential difference in atmospheric NH3 acquisition that is consistent with existing field differences in nitrogen concentrations and δ15N between mosses and lichens in general. This study clarifies the δ15N enrichment of cryptogams resulting from one of the most important nitrogen pathways for Antarctic vegetation.
Keywords: Antarktis; fugler; kjemiske analyser; kryptogamer; lav; moser; planter; seler; økologi

Patchy Lakes and Topographic Origin for Fast Flow in the Recovery Glacier System, East Antarctica - Diez, Anja; Matsuoka, Kenichi; Jordan, Tom A; Kohler, Jack; Ferraccioli, Fausto; Corr, Hugh F; Olesen, Arne V; Forsberg, René; Casal, Tania G (Journal of Geophysical Research: Earth Surface, 2019)
The Recovery subglacial basin, with its largest glacier Recovery Glacier, has been identified as potentially the biggest contributor to future sea level rise from East Antarctica. Subglacial lakes along the main trunk have been detected from satellite data, with four giant lakes (Recovery Lakes A, B, C, and D) located at the onset of the fast ice flow (≥15 m/yr) and multiple smaller lakes along the glacier. The presence of subglacial water potentially plays a key role in the control of fast ice flow of Recovery Glacier. We present new insights on the Recovery Lakes from airborne radar data collected in 2013 and 2015. Using an adjusted classification scheme, we show that a single large area consisting of smaller lakes connected by likely saturated sediment, referred to as Lake AB, exists in the originally proposed area of the Recovery Lakes A and B. We estimate that the current size of Lake AB is ∼4,320 km2. Water likely leaks from the western shore of Lake AB lubricating the bed initiating fast ice flow at this location. The difference in the outlines of Lake AB and the Lakes A and B previously derived from surface features suggested that a larger paleolake existed here in the past. From our data, we find Recovery Lake C to be dry; we attribute fast ice flow originating from this area to be due to a topographic step and thus an increase in ice thickness rather than enhanced lubrication at the bed.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; radar observasjoner; satellite bilder; subglasial innsjø; topografi

Variability of Sediment Accumulation Rates in an Antarctic Fjord - Eidam, Emily F.; Nittrouer, Charles; Lundesgaard, Øyvind; Homolka, Khadijah; Smith, Craig (Geophysical Research Letters, 2019)
Fjords on the West Antarctic Peninsula (WAP) serve as sediment traps, preserving histories of glacial sediment supply. Regional warming trends are expected to change sediment supplies, altering water quality, depositional history, and ecosystem drivers. Our ability to assess magnitudes of these changes is limited by sparse data on modern sediment accumulation. Twelve new cores and four existing cores from Andvord Bay were used to characterize variability in sediment accumulation rates. These range from 1.5 to 7.9 mm/year (0.12 to 0.56 g·cm−2·year−1). Spatial differences and a weak down-fjord gradient in rates suggest diverse sediment sources, including from outside the fjord. This data set provides a comprehensive assessment of sedimentation during the past century, indicating little change in rates due to recent WAP warming, and sets a benchmark for assessing climate-related changes in sediment delivery and ecosystem drivers (e.g., burial disturbance) in the fjord over coming decades.
Keywords: Antarktis; akkumulasjon; bentiske organismer; biodiversitet; fjord; glasiologi; sedimenter; sedimentologi; tidevannsbreen

Quantarctica 3 released - Matsuoka, Kenichi; Skoglund, Anders; Roth, George; Melvær, Yngve; Tronstad, Stein (Fram forum, 2019)
Keywords: Antarktis; geofysikk; geografi; glasiologi; innlandsis; kartografi; satellite bilder

A note on digital elevation model smoothing and driving stresses - McCormack, Felicity S; Roberts, Jason L; Jong, Lenneke M; Young, Duncan A; Beem, Lucas H (Polar Research, 2019)
Ice-flow fields, including the driving stress, provide important information on the current state and evolution of Antarctic and Greenland ice-sheet dynamics. However, computation of flow fields from continent-scale DEMs requires the use of smoothing functions and scales, the choice of which can be ad hoc. This study evaluates smoothing functions and scales for robust calculations of driving stress from Antarctic DEMs. Our approach compares a variety of filters and scales for their capacity to minimize the residual between predicted and observed flow direction fields. We find that a spatially varying triangular filter with a width of 8–10 ice thicknesses provides the closest match between the observed and predicted flow direction fields. We use the predicted flow direction fields to highlight artefacts in observed Antarctic velocities, demonstrating that comparison of multiple observational data sets has utility for quality control of continent-scale data sets.
Keywords: Antarktis; geofysikk; glasiologi; innlandsis; isbreer; istykkelse

Review of The life of José María Sobral: scientist, diarist, and pioneer in Antarctica, by Mary R. Tahan (2018). Cham, Switzerland: Springer International Publishing. 336 pp. ISBN 978-3-319-67267-0 - Millar, Pat (Polar Research, 2019)
Keywords: Antarktis; Otto Nordenskjöld; bokanmeldelser; dagbøker; ekspedisjoner; geodesi; magnetisme; meteorologi; oppdagelsesreiser

First evidence of a tetrapod footprint from the Triassic of northern Victoria Land, Antarctica - Mörs, Thomas; Niedźwiedzki, Grzegorz; Crispini, Laura; Läufer, Andreas; Bomfleur, Benjamin (Polar Research, 2019)
Here, we report on a tetrapod footprint from the Transantarctic Basin in the far north of Victoria Land, which marks the first record of terrestrial vertebrates for this region. The single specimen derives from a previously unknown lithological unit of Middle or Late Triassic age of the Beacon Supergroup in the Helliwell Hills in the central Rennick Glacier area. It differs in both size and morphology clearly from Middle Triassic trackway types from the upper Fremouw Formation of the Queen Alexandra Range in southern Victoria Land, and likely represents a primitive amniote, procolophonid or therapsid. The footprint is the third evidence of fossil vertebrate trackways in Antarctica.
Keywords: Antarktis; fossiler; paleobiologi; paleontologi; terrestriske virveldyr

Very Strong Atmospheric Methane Growth in the 4 Years 2014–2017: Implications for the Paris Agreement - Nisbet, Euan G; Manning, Martin; Dlugokencky, Ed; Fisher, Rebecca; Lowry, Dave; Michel, Sylvia; Myhre, Cathrine Lund; Platt, Stephen Matthew; Allen, Grant; Bousquet, Philippe; Brownlow, Rebecca; Cain, Michelle; et al. (Global Biogeochemical Cycles, 2019)
Atmospheric methane grew very rapidly in 2014 (12.7 ± 0.5 ppb/year), 2015 (10.1 ± 0.7 ppb/year), 2016 (7.0 ± 0.7 ppb/year), and 2017 (7.7 ± 0.7 ppb/year), at rates not observed since the 1980s. The increase in the methane burden began in 2007, with the mean global mole fraction in remote surface background air rising from about 1,775 ppb in 2006 to 1,850 ppb in 2017. Simultaneously the 13C/12C isotopic ratio (expressed as δ13CCH4) has shifted, now trending negative for more than a decade. The causes of methane's recent mole fraction increase are therefore either a change in the relative proportions (and totals) of emissions from biogenic and thermogenic and pyrogenic sources, especially in the tropics and subtropics, or a decline in the atmospheric sink of methane, or both. Unfortunately, with limited measurement data sets, it is not currently possible to be more definitive. The climate warming impact of the observed methane increase over the past decade, if continued at >5 ppb/year in the coming decades, is sufficient to challenge the Paris Agreement, which requires sharp cuts in the atmospheric methane burden. However, anthropogenic methane emissions are relatively very large and thus offer attractive targets for rapid reduction, which are essential if the Paris Agreement aims are to be attained.
Keywords: Antarktis; atmosfæren; atmosfærisk metan; fossilt brensel; global klimamodell; global oppvarming; klimaendringer; klimagasser; metanisotoper; metanutslipp; meteorologi; polarområdene

Influence of Summer Sublimation on δD, δ18O, and δ17O in Precipitation, East Antarctica, and Implications for Climate Reconstruction From Ice Cores - Pang, Hongxi; Hou, Shugui; Landais, Amaelle; Masson-Delmotte, Valérie; Jouzel, Jean; Steen-Larsen, Hans Christian; Risi, Camille; Zhang, Wangbin; Wu, Shuangye; Li, Yuansheng; An, Chunlei; Wang, Yetang; et al. (Journal of Geophysical Research: Atmospheres, 2019)
In central Antarctica, where accumulation rates are very low, summer sublimation of surface snow is a key element of the surface mass balance, but its fingerprint in isotopic composition of water (δD, δ18O, and δ17O) remains unclear. In this study, we examined the influence of summer sublimation on δD, δ18O, and δ17O in precipitation using data sets of isotopic composition of precipitation at various sites on the inland East Antarctica. We found unexpectedly low δ18O values in the summer precipitation, decoupled from surface air temperatures. This feature can be explained by the combined effects of weak or nonexistent temperature inversion and moisture recycling associated with sublimation-condensation processes in summer. Isotopic fractionation during the moisture-recycling process also explains the observed high values of d-excess and 17O-excess in summer precipitation. Our results suggest that the local cycle of sublimation-condensation in summer is an important process for the isotopic composition of surface snow, water vapor, and consequently precipitation on inland East Antarctica.
Keywords: Antarktis; geofysikk; iskjerner; paleoklimatologi; stabile isotoper

Subglacial Geology and Geomorphology of the Pensacola-Pole Basin, East Antarctica - Paxman, Guy J G; Jamieson, Stewart S R; Ferraccioli, Fausto; Jordan, Tom A; Bentley, Michael J; Ross, Neil; Forsberg, René; Matsuoka, Kenichi; Steinhage, Daniel; Eagles, Graeme; Casal, Tania G (Geochemistry, Geophysics, Geosystems, 2019)
The East Antarctic Ice Sheet (EAIS) is underlain by a series of low-lying subglacial sedimentary basins. The extent, geology, and basal topography of these sedimentary basins are important boundary conditions governing the dynamics of the overlying ice sheet. This is particularly pertinent for basins close to the grounding line wherein the EAIS is grounded below sea level and therefore potentially vulnerable to rapid retreat. Here we analyze newly acquired airborne geophysical data over the Pensacola-Pole Basin (PPB), a previously unexplored sector of the EAIS. Using a combination of gravity and magnetic and ice-penetrating radar data, we present the first detailed subglacial sedimentary basin model for the PPB. Radar data reveal that the PPB is defined by a topographic depression situated ~500 m below sea level. Gravity and magnetic depth-to-source modeling indicate that the southern part of the basin is underlain by a sedimentary succession 2–3 km thick. This is interpreted as an equivalent of the Beacon Supergroup and associated Ferrar dolerites that are exposed along the margin of East Antarctica. However, we find that similar rocks appear to be largely absent from the northern part of the basin, close to the present-day grounding line. In addition, the eastern margin of the basin is characterized by a major geological boundary and a system of overdeepened subglacial troughs. We suggest that these characteristics of the basin may reflect the behavior of past ice sheets and/or exert an influence on the present-day dynamics of the overlying EAIS.
Keywords: Antarktis; Sydpolen; Sørpolen; geofysikk; geomorfologi; glasiologi; innlandsis; subglasial geologi; subglasial topografi

Comparison of elastic moduli from seismic diving-wave and ice-core microstructure analysis in Antarctic polar firn - Schlegel, Rebecca; Diez, Anja; Löwe, Henning; Mayer, Christoph; Lambrecht, Astrid; Freitag, Johannes; Miller, Heinrich; Hofstede, Coen; Eisen, Olaf (Annals of Glaciology, 2019)
We compared elastic moduli in polar firn derived from diving wave refraction seismic velocity analysis, firn-core density measurements and microstructure modelling based on firn-core data. The seismic data were obtained with a small electrodynamic vibrator source near Kohnen Station, East Antarctica. The analysis of diving waves resulted in velocity–depth profiles for different wave types (P-, SH- and SV-waves). Dynamic elastic moduli of firn were derived by combining P- and S-wave velocities and densities obtained from firn-core measurements. The structural finite-element method (FEM) was used to calculate the components of the elastic tensor from firn microstructure derived from X-ray tomography of firn-core samples at depths of 10, 42, 71 and 99 m, providing static elastic moduli. Shear and bulk moduli range from 0.39 to 2.42 GPa and 0.68 to 2.42 GPa, respectively. The elastic moduli from seismic observations and the structural FEM agree within 8.5% for the deepest achieved values at a depth of 71 m, and are within the uncertainty range. Our observations demonstrate that the elastic moduli of the firn can be consistently obtained from two independent methods which are based on dynamic (seismic) and static (tomography and FEM) observations, respectively, for deeper layers in the firn below ~10 m depth.
Publisher: Cambridge University Press
Keywords: Antarktis; glasiologi; seismologi

Project and Community Management in Polar Sciences – Challenges and Opportunities - Werner, Kirstin; Zaika, Yulia; Pavlov, Alexey K; Lidström, Sven; Pope, Allen; Badhe, Renuka; Brückner, Marlen; Cristini, Luisa (Adv. Geosci., 2019)
Because geoscientific research often occurs via community-instigated bursts of activity with multi-investigator collaborations variously labelled as e.g., years (The International Polar Year IPY), experiments (World Ocean Circulation Experiment WOCE), programs (International Ocean Discovery Program), missions (CRYOSAT spacecraft), or decades (The International Decade of Ocean Exploration IDOE), successful attainment of research goals generally requires skilful scientific project management. In addition to the usual challenges of matching scientific ambitions to limited resources, on-going coordination and specifically project management, planning and implementation of polar science projects often involve many uncertainties caused by, for example, unpredictable weather or ocean and sea ice conditions, large-scale logistical juggling; and often these collaborations are spatially distributed and take place virtually. Large amounts of funding are needed to procure the considerable infrastructure and technical equipment required for polar expeditions; permissions to enter certain regions must be requested; and potential risks for expedition members as well as technical issues in extreme environments need to be considered. All these aspects are challenging for polar science projects, which therefore need a well thought-through program including a realistic alternative “plan B” and possibly also a “plan C” and “plan D”. The four most challenging overarching themes in polar science project management have been identified: international cooperation, interdisciplinarity, infrastructure, and community management. In this paper, we address ongoing challenges and opportunities in polar science project management based on a survey among 199 project and community managers and an additional of 85 project team members active in the field of polar sciences. Case studies and survey results are discussed with the conclusive goal to provide recommendations on how to fully reach the potential of polar sciences project and community management.
Publisher: Copernicus Publications
Keywords: Antarktis; geovitenskap; internasjonal samarbeid; klimaendringer; miljøendringer; polarområdene

A nematode in the mist: Scottnema lindsayae is the only soil metazoan in remote Antarctic deserts, at greater densities with altitude - Zawierucha, Krzysztof; Marshall, Craig J; Wharton, David; Janko, Karel (Polar Research, 2019)
A decrease in biodiversity and density of terrestrial organisms with increasing altitude and latitude is a well-known ecogeographical pattern. However, studies of these trends are often taxonomically-biased toward well-known organisms and especially those with relatively large bodies, and environmental variability at the local scale may perturb these general effects. Here, we focus on understudied organisms—soil invertebrates—in Antarctic deserts, which are among the driest and coldest places on Earth. We sampled two remote Antarctic sites in the Darwin Glacier area and established an altitudinal gradient running from 210 to 836 m a.s.l. We measured soil geochemistry and organic matter content and linked these parameters with the presence of soil invertebrates. We found three general outcomes, two of which are consistent with general assumptions: (a) the hostile climatic condition of the Darwin Glacier region supports an extremely low diversity of soil metazoans represented by a single nematode species—Scottnema lindsayae; (b) soil geochemistry is the main factor influencing distribution of nematodes at the local scale. Contrary to our expectations, a positive correlation was found between nematode density and altitude. This last observation could be explained by an additional effect of soil moisture as we found this increased with altitude and may be caused by orographic clouds, which are present in this region. To the best of our knowledge such effects have been described in tropical and temperate regions. Potential effect of orographic clouds on soil properties in polar deserts may be a fruitful area of ecological research on soil fauna.
Keywords: Antarktis; biodiversitet; geokjemi; jord; metazoan; rundormer; økogeografi; økosystemer

Verification and Improvement of the Ability of CFSv2 to Predict the Antarctic Oscillation in Boreal Spring - Zhang, Dapeng; Huang, Yanyan; Sun, Bo; Li, Fei; Wang, Huijun (Advances in Atmospheric Sciences, 2019)
The boreal spring Antarctic Oscillation (AAO) has a significant impact on the spring and summer climate in China. This study evaluates the capability of the NCEP’s Climate Forecast System, version 2 (CFSv2), in predicting the boreal spring AAO for the period 1983–2015. The results indicate that CFSv2 has poor skill in predicting the spring AAO, failing to predict the zonally symmetric spatial pattern of the AAO, with an insignificant correlation of 0.02 between the predicted and observed AAO Index (AAOI). Considering the interannual increment approach can amplify the prediction signals, we firstly establish a dynamical–statistical model to improve the interannual increment of the AAOI (DY AAOI), with two predictors of CFSv2-forecasted concurrent spring sea surface temperatures and observed preceding autumn sea ice. This dynamical–statistical model demonstrates good capability in predicting DY AAOI, with a significant correlation coefficient of 0.58 between the observation and prediction during 1983–2015 in the two-year-out cross-validation. Then, we obtain an improved AAOI by adding the improved DY AAOI to the preceding observed AAOI. The improved AAOI shows a significant correlation coefficient of 0.45 with the observed AAOI during 1983–2015. Moreover, the unrealistic atmospheric response to March–April–May sea ice in CFSv2 may be the possible cause for the failure of CFSv2 to predict the AAO. This study gives new clues regarding AAO prediction and short-term climate prediction.
Keywords: Antarktis; atmosfæren; klimatologi; meteorologi